Role of Information Technology Infrastructure on Adoption of Electronic Procurement in State Corporations in Kenya - Moses Kabiru Mugwe (Economit Journal: Scientific Journal of Accountancy, Management and Finance, 2023)
The aim of this study was to assess the role played by information technology infrastructure in enhancing the adoption of electronic procurement in state corporations in Kenya. The study focused on ICT software infrastructure and hardware infrastructure. Using a descriptive research approach, the study surveyed 187 procurement managers from the 187 state corporations in Kenya. A structure questionnaire was used to collect the data which was analyzed using descriptive and inferential statistics. The findings revealed that ICT infrastructure was essential in enhancing the adoption of electronic procurement in state corporations. It was revealed that through the ICT software infrastructure such as the operating systems, it becomes viable to integrate procurement functions in the systems. ICT hardware on the other hand promotes the use of procurement systems thus enabling embrace of electronic procurement. The study recommended the need for the government to support the state corporations in integrating and adopting electronic procurement through funding them to acquire the appropriate ICT hardware and software infrastructure that is essential for the integration of e-procurement.